ETHNICITY AND ELECTORAL BEHAVIOUR IN NIGERIA - Nnabuihe, Nwachukwu Sunny; Aghemalo, Austin; Okebugwu, Nwosu Ezekwesiri (European Scientific Journal, ESJ, 2014)
It is rather an indisputable fact that ethnicity has marred politics in Nigeria. With ample of data, it is evidently shown that ethnicity determines the choice of votes and voter‘s decisions in electioneering in Nigeria. The electoral choice of Nigerians are ethnically coloured as party formations are ethnically designated and motivated. The analysis below shows that political parties in Nigeria do not have national platform hence political party that is formed from the majority ethnic group dominate the said region and 2/3 majority is almost difficult to attain except if major parties go alliance. The study began with an examination of the history and electoral behaviours of Nigerians. The result of the first and second republics and their voting patterns have been mapped using the results of these elections to determine the ethnic colouration of the electorate. More so, the researchers further their findings to identifying institutional structures that have aided ethnicity to mar democratic consolidation in Nigeria, various approaches were adopted to study ethnicity in Nigeria and findings showed that ethnicity is the major factor militating against the evolution of the truly modern and democratic nation where the interest, wellbeing and the rights of people are protected.